Exergoeconomic analysis of corncob gasification integrated to a power generation system: Case study in Colombia - Fandiño, Jorge Mario Mendoza; Julio, Jesús David Rhenals; Gomez, Adrián Enrique Ávila; Padilla, Elías Ricardo Durango [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2021)
The aim of this work was to carry out an exergoeconomic model of corn cob gasification using water vapor as a gasifying agent coupled to an internal combustion engine to generate electricity. Initially, the physicochemical characterization of the samples was performed by immediate analysis, elemental analysis and higher heating value (HHV). The characterization output was 65.23 % for volatile material, 16.54 % for fixed carbon and 13.53 MJ/kg of HHV. A simulation was made using Aspen HYSYS software, obtaining a gas with a heating value of 12.41 MJ/kg. Then, an exergoeconomic generation cost of 0.040 USD/kWh was calculated for a 10.1 MW system, with an internal rate of return (IRR) of 65.75 % for a period of 20 years. Finally, an energetic optimization of the system integration was performed using the response surface methodology (RSM) in the Statgraphics software, obtaining a generation potential of 10.55 MW, a generation cost of 0.037 USD/kWh and an exergetic efficiency 45.8 % with which an IRR of 68.71 %. Additionally, the plant size impact on the generation cost and the IRR was calculated, finding that the balance size was 770 kW for an incoming mass flow of 360 kg/h. The assessed costs are type 3 and therefore have an uncertainty of 15 %.
Análise exergoeconômica da gasificação de sabugo de milho integrado em um sistema de geração de energia: Estudo de caso na Colômbia
Keywords: Biomass; Exergy; Optimization; Simulation